Individual differences in eating motives and environmental attitudes. Issue 1 (31st December 2022) - Hopwood, Christopher J.
ABSTRACT: Research shows that plant-based diets help reduce the impacts of climate change and that people who adopt plant-based diets tend to have more proenvironmental attitudes. However, recent work has highlighted that people can have very different reasons to eat meat or be vegetarian, opening up new opportunities to understand how eating motives intersect with attitudes about the environment. In this study, associations were examined between four motivations to eat meat (natural, necessary, normal, and nice), three motivations to be vegetarian (health, the environment, and animal rights), and seven environmental attitudes (knowledge, connectedness to nature, intrinsic, extrinsic and social motives for sustainable behavior, faith in growth, and biospherism) in a community sample from the US (N = 1, 234). Distinct profiles of environmental attitude were found across different motivations to eat meat. Ethical motives to be vegetarian were more strongly related to proenvironmental attitudes than health motives. These results move beyond general associations between meat reduction and proenvironmental attitudes by showing that individual differences in dietary motivations have different implications for how individual think about and interact with the environment. Implications for future research are discussed.